Сигналы речевой агрессии в текстах научной и публицистической рецензий : магистерская диссертация - Порозова, И. Е. (2018)
The dissertation considers verbal aggression as a phenomenon of modern linguistics, offers a classification of means of expressing verbal aggression. Signals of verbal aggression in the texts of scientific and journalistic reviews are singled out on the basis of empirical research. The conclusion was made about increasing the level of aggressiveness of the modern cultural and speech environment, about penetration of verbal aggression into written texts, including texts of scientific functional style. === В магистерской диссертации рассматривается речевая агрессия как явление современной лингвистики, предлагается классификация средств выражения речевой агрессии. На основе эмпирического исследования выделяются сигналы речевой агрессии, наиболее характерные для текстов научной и публицистической рецензий. В результате исследования сделан вывод о повышении уровня агрессивности современной культурно-речевой среды, о проникновении речевой агрессии в письменные тексты, в том числе и в тексты научного функционального стиля.